2022
DOI: 10.3389/fenvs.2022.820615
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Pattern and Influencing Factors of Drought Impacts on Agriculture in China

Abstract: Agricultural drought disaster is a major natural disaster affecting economic and social development. It is of significance to investigate the spatial–temporal pattern and the dominant influence of natural and human factors on agricultural drought disasters for drought hazard relief. In this study, Mann–Kendall test was adopted to explore the evolution of agricultural drought disasters. Random forest algorithm, which integrates feature importance and accumulated local effects plot, was applied to quantify the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In contrast to Dai et al (2022), Deng et al (2022), Dupla et al (2022), andParmar et al (2022), it has been proved that technological modernization does not necessarily lead to a gap between the economy and ecology, but on the contrary, can help to bridge this gap. So, for example, the development of AgroTech simultaneously increases the added value created in the agroindustrial complex (economic advantage) and increases the productivity of natural (organic) agriculture (environmental advantage).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast to Dai et al (2022), Deng et al (2022), Dupla et al (2022), andParmar et al (2022), it has been proved that technological modernization does not necessarily lead to a gap between the economy and ecology, but on the contrary, can help to bridge this gap. So, for example, the development of AgroTech simultaneously increases the added value created in the agroindustrial complex (economic advantage) and increases the productivity of natural (organic) agriculture (environmental advantage).…”
Section: Discussionmentioning
confidence: 87%
“…The existing literature also reveals in sufficient detail the essence and features of agriculture in the era of artificial intelligence, embodied in the practice of AgroTech. In the works of Dai et al (2022), Deng et al (2022), Dupla et al (2022), andParmar et al (2022), it is noted that as technological modernization strengthens, the gap between the economy and ecology increases. If this gap is quite large and obvious in industry, then in agriculture it has been most clearly manifested only in the process of the Fourth Industrial Revolution.…”
Section: Environmental Decision-making In Environmental Business-mana...mentioning
confidence: 99%
“…Reference is made to China's 'the 14th Five-Year Plan for Green Industrial Development' and the research results of Deng et al [18]. Industrial green development can be defined as a concept guided by the principles of green development, with a focus on promoting high-quality growth and prioritizing actions that reduce pollution, lower carbon emissions, and enhance efficiency through synergistic means.…”
Section: Research Data and Explanation 221 Explained Variable: Indust...mentioning
confidence: 99%
“…Many studies also found that natural disasters significantly negatively impact economic development (Cavallo et al, 2013;Abbas Khan et al, 2019;Qureshi et al, 2019;Deng et al, 2022), making it difficult for individuals to maintain normal economic activities in a poor external environment, thereby indirectly affecting household wealth accumulation. More importantly, natural disasters also directly affect household wealth.…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%